Description of the Level of Stress on the Performance of South Kalimantan Regional Police's Biddokkes Personnel During the Covid-19 Pandemic - M. Tajaruddin; Merlin Karinda; Imam Hidayat (KUNKUN: Journal of Multidisciplinary Research, 2024)
Now the National Police no longer only handles crime, street crime, white collar crime, radicalism and drug problems, but also as the National Task Force for the Acceleration of Handling Covid-19, the National Police has a number of additional tasks, including accelerating vaccination for the community. In particular, the South Kalimantan Regional Police Biddokkes work unit has carried out vaccination efforts for the community in South Kalimantan Province, this has increased the workload for South Kalimantan Regional Police Biddokkes personnel with various main tasks that are inherent in the general Health Biddokkes function. This research is a descriptive method with a cross-sectional approach, aimed at finding out the description of the level of stress on the performance of the South Kalimantan Regional Police's Medical and Health Services personnel during the Covid-19 pandemic. The sampling technique was carried out using purposive sampling with a sample size of 82 respondents.The research results showed that the highest percentage were personnel with moderate levels of stress, 48 ​​(58%), the lowest percentage with very severe levels of stress, 12 (15%), normal stress, 8 (10%), mild stress, 14 (17%), and severe stress. 12 (15%). It is recommended to the Head of Biddokkes to optimize counseling guidance so that the stress experienced by personnel can be controlled well, how to manage stress properly, assignments are not excessive, and the importance of motivation and support from the family